Un programa de pensamiento prosocial (PPS) para la intervención de la drogodependencia en el medio penitenciario : análisis de resultados. - Rodríguez, Francisco Javier; Álvarez, Esteban; Castro, Dolores; Carbonero, Patricia G.; Granda, Eva H.; Rodríguez Franco, Luis (Acta Colombiana de Psicología, 2001)
The intervention in relationship to prevention and treatment of the criminal behavior, mainly of that one related to drug addiction is one of the challenges of the Justice System. The purpose of this study was to show the efficiency of the prosocial orientation in the jail system and in other places with abusers of multiple drugs during the period of cleaning. The sample were 19 inmates of Villabona (Asturias) Jail, recidivist and with an age average over 30 years old. The results do not show statistical significant, but a social efficiency that allow ordering the necessary steps to get it.